Superaleaciones para soldaduras dentales - Prilutzky, H.; Palacios, Tulio Alfredo; Riesgo, O. (Comisión Nacional de Energía Atómica; Argentina, 1973)
Fil: Prilutzky, H. Comisión Nacional de Energía Atómica; Argentina